Islam dan Migrasi Manusia (Tafsir Al-Isra' Ibnu Asyur : 70 dan Yasin : 41) - Abdul Khamid (Universitas Darussalam Gontor, 2024)
Mobility, which is often referred to as Migration, is not something foreign to our ears, however, this incident is increasingly being discussed and carried out by people with various purposes, for example, there are those who seek Allah's sustenance on another earth, there are those who find a soul mate from a distant person who is forced to stay. and many more. Previously, migration was still carried out manually, such as riding on camels, horses, and some walked hundreds of hundreds of kilometers just to make the journey. However, as time progresses, humans are also given physical perfection as well as mental perfection, which in turn humans are inspired by Allah SWT, in this case the author discusses science. These knowledges are utilized and developed to make the journey easier, this is the basis for the author to raise the theme of Human Migration. This explanation has also been written in the interpretation of a figure named Ibn Asyur regarding this matter in Qs. Al-Isra' verse 70 and Qs. Yasin Verse 40 about human mobility from time to time. Thus, human travel can be made easier with the latest discoveries in the form of motorbikes, cars used for land and ships for crossing the sea. The author in this research presents new and interesting analysis and findings to look at regarding these two verses which have not previously been interpreted in previous interpretations